A comparative study of contemporary user involvement within healthcare systems across England, Poland and Slovenia. Issue 5 (17th August 2015) - Lichon, Mateusz; Kavcic, Matic; Masterson, Daniel
Abstract : Purpose: – The purpose of this paper is to explore how healthcare-users' engagement is perceived, how it occurs and how these perceptions differ between three European countries: England, Poland and Slovenia, using the concepts of voice, choice and coproduction. Design/methodology/approach: – This comparative, qualitative study is based on a review of legal documents, academic literature and semi-structured interviews conducted in October and November 2011. A research sample consisted of 21 interviewees representing various stakeholders including healthcare-users, doctors and managers. Primary and secondary data were analysed using theoretical thematic analysis. Emerging themes were identified from the interviews and related to the indicators describing healthcare-users' involvement in the voice, choice and coproduction model. Findings: – Results of the comparative qualitative research suggest that the healthcare-users' influence is strongly grounded in England where the healthcare system and professionals are prepared to include healthcare-users in the decision-making process. In Slovenia, cultural development of healthcare-users' involvement seems to proceed the institutional development. In Poland, institutions are ready to involve healthcare-users in decision-making process although the cultural desirability of involving users among doctors and patients is lacking. Originality/value: – The notion of user involvement is increasingly gaining importance and research attention, yet there is still little known about the way cultural, political, historical differences between various European countries influence it. This paper explores this little known area using the original approach of user involvement (Dent et al., 2011) with input from various stakeholders including patients, healthcare representatives and academics.